Persepsi Karyawan PT. Guguk Tinggi Coal Sawahlunto Terhadap Penerapan Norma Keselamatan dan Kesehatan Kerja - Andes Andes; Rijal Abdullah; Murad Murad (Journals Mining Engineering : Bina Tambang, 2018)
PT. Guguk Tinggi Coal, is a coal mining company located in salak village, Talawi, Sawahlunto city, West Sumatra province. In executing the mining accidents that often occur is influenced by the perception of employee knowledge about K3 norms and the high level of accident risk that occurs. The purpose of this study to reveals the perception of employes PT. Guguk Tinggi Coal About the safety norm, Reveals the risk persentage of work accident occurring at PT. Guguk Tinggi Coal.Data collected or obtained directly from the respondents with direct observation in the field and direct interviews with employees that competent in companies and have relation with the object of research. The data taken are the conditions in the environment (mining area to the stock of the workplace files) as well as potential hazards that may occur, the employee's knowledge of safety norms and work programs of K3 management, workers' responses to the programs undertaken by K3 management.The results obtained are the employee's knowledge about K3 and how to evaluate the work activities are still low with the results obtained by the questionnaire test with a value of 3.35 for the implementation and 3.21 for the evaluation of this category is still quite good, there are still factors of work accident from unsafe conditions and unsafe actions, PT.Guguk Tinggi Coal should form a special management for K3 and provide training and guidance on the importance of occupational safety and health, management is also required to always evaluate the activities of the workers in intensive mining activities.